Glacier Surge Dynamics on Western Axel Heiberg Island, Nunavut - Lauzon, Benoît (Université d'Ottawa / University of Ottawa, 2022)
Surge-type glaciers experience cyclical variations between long periods of slow flow, followed by shorter periods of rapid flow. These glaciers have been thoroughly analysed in many regions, but detailed studies of surging in the Canadian Arctic are lacking. This thesis provides the first comprehensive reconstruction of the dynamics of Iceberg and Airdrop glaciers, located on western Axel Heiberg Island, and reveals detailed observations of a surge for the first time in the Canadian Arctic. A variety of remotely sensed data, including historical aerial photographs, declassified intelligence satellite photographs, optical satellite imagery (e.g., ASTER, Landsat), and synthetic aperture radar data (e.g., ERS-1, ERS-2) were used to quantify changes in terminus position, ice velocity, and ice thickness since the 1950s. A surge initiated at the terminus of Iceberg Glacier in 1981 and terminated in 2003, suggesting an active phase length of 22 years. High surface velocities, peaking at ~2300 m a⁻¹ at the terminus in summer 1991, were accompanied by a terminus advance of >7 km over the period 1981-1997 and a large transfer of mass down-glacier, causing significant median surface elevation changes reaching >3 ± 1 m a⁻¹ across the entire trunk width. The ensuing quiescent period has seen a continual decrease in flow rates to an average centreline velocity of 11.5 m a⁻¹ in 2020-2021, a gradual steepening of the glacier surface, and a terminus retreat of >2.5 km. Observations on Airdrop Glacier show a continuous advance totalling ~6 km since 1950 and notably less variability in its surface velocities in comparison to Iceberg Glacier. This advance can be attributed to consistently high flow rates of Airdrop’s entire surface, resulting in significant thickening near its terminus since at least 1977. However, velocities have more than halved within the last 15 years, but without any clear evidence of previous fast flow events, we cannot confirm whether Airdrop’s behaviour is cyclic in nature and therefore ...